Pakistan : Third Review Under the Extended Arrangement and Request for Waiver of Nonobservance of Performance Criterion, and Request for Modification of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2014)
This Paper discusses Pakistan's Third Review Under the Extended Arrangement and Request for Waiver of Nonobservance of Performance Criterion (PC).The economy is showing signs of improvement. The FY2013/14 growth projection has been revised upward from 3.1 percent to 3.3 percent, as economic indicators continue to show better-than-expected performance. For FY2014/15, the economy is forecast to expand by about 4 percent. All quantitative PCs were met with the exception of the ceiling on Net Domestic Assets of the State Bank of Pakistan, which was missed by a small margin. On the basis of Pakistan's performance under the extended arrangement, the IMF staff supports the authorities' request for completion of the third review under the arrangement.